Polytechnic edition published by graduates of Harbin Institute of Technology - Kradin, Nikolai (project baikal, 2021)
This article discusses and analyzes the material relating to the life and creative activity of the former graduates of Harbin Institute of Technology, who came to Australia. The author analyzes the content of materials of all 17 journal issues published in 1969-2004. Examples of works by graduates of HIT who came to live in Russia, Europe, Australia and America are given; their memories about the institute, about the teachers and the educational process are analyzed. In particular, the author talks about five commemorative editions of Polytechnic devoted to the anniversaries of the HIT and the journal.
Keywords: Harbin Institute of Technology; Shanghai; Australia and Sydney; engineers; editorial board of the journal; authors of the articles